Pelatihan Online Metode Kuantitatif: Model Runtun Waktu Terapan - Aliasuddin Aliasuddin; Nanda Rahmi; Mirza Tabrani; Nashrillah Nashrillah; Kamal Fachrurrozi (Jurnal Pemberdayaan Umat, 2022)
Purpose: the aim of this training is to improve the skill and ability of participants to apply quantitative method of time series model in their researchers by using zoom application. Method: the descriptive analysis is used to analyze this activity based on the responses of the participants in this training. Results: based on the results of the training on the quantitative method of applied time series model, it can be concluded that this activity is very important so that participants can understand data and be able to enter data correctly so as not to cause problems when estimating and processing other statistical data. Contribution: in general, the participants felt that they were very good at implementing this activity and they hoped that there would be additional activities that were more focused on practice so that participants could apply various time series models in research and teaching at their respective institutions. ?t is recommended that participants need further training related to the application of the theories that have been presented in this training in order participants are able to publish their papers in international indexed journals.